Envisioning Social Justice With Criminalized Young Adults - Weaver, Beth (The British journal of criminology, 2024)
Rather than attending to the social harms underpinning youth offending, justice responses tend to amplify and entrench them. While perhaps less noticeable, inequalities further reside in the systematic disparities in criminalized young adults’ opportunities to influence policy and practice and to have control of the choices concerning their present and their future. Resultantly, perhaps, there is a significant disconnect between policy and practice directed towards this group, their lived realities and developmentally specific needs. This article reports on a design-led, participatory study involving 12 criminalized young adults, aged 18-25, oriented to listening to, and learning from, their experiences and visions of social justice in order to influence more socially just responses to offending than we have at present.